2006
DOI: 10.1111/j.1475-6773.2006.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Physician Reimbursement Strategies Associated with Processes of Care and Patient Satisfaction for Patients with Diabetes in Managed Care?

Abstract: Physician reimbursement strategies are associated with diabetes care processes, although their independent contributions are difficult to assess, due to high correlation with physician organizational model. Regardless of causality, a group's use of quality/satisfaction scores to determine physician compensation may indicate delivery of high-quality diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
15
1
1
Order By: Relevance
“…Several studies conducted in the United States have demonstrated that practices that primarily pay their physicians through direct salary provide strong diabetes care [21-23]. The CHC's payment structure, organizational structure and care delivery approach which includes team care, focused clinics and the use of an EMR is likely a strong contributor to the observed differences in quality of diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in the United States have demonstrated that practices that primarily pay their physicians through direct salary provide strong diabetes care [21-23]. The CHC's payment structure, organizational structure and care delivery approach which includes team care, focused clinics and the use of an EMR is likely a strong contributor to the observed differences in quality of diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Health system factors in particular have received very little attention for their potential direct and indirect effects upon diabetes and depression treatment, quality of care and outcomes. The impact of these potentially confounding factors, such as benefit structure, co-pay amounts, requirements for pre-approval of specialist care, and the use of electronic medical record systems [2729,37,38] are difficult to take into consideration in studies of single health care plans.…”
Section: Discussionmentioning
confidence: 99%
“…30 In the USA, FFS payment mechanisms have been found to be associated with poorer adherence to recommended processes of diabetes care and may also lead to relatively poor documentation of unreimbursed services. 31 Unlike in the UK, the US health system is neither based on primary care nor does it protect its financing from hospital and subspecialty services. These system-level differences, coupled with the UK investments in primary care, are likely among the determinants of the differences in quality observed here.…”
Section: Discussionmentioning
confidence: 99%